2019
DOI: 10.2147/copd.s202580
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of cough and mucus on COPD patients: primary insights from an exploratory study with an Online Patient Community</p>

Abstract: Background: Qualitative research provides real-life information on patients’ condition and facilitates informed design of future clinical studies. Objective: We used Online Communities as a qualitative research tool to evaluate the effect of cough and mucus on COPD patients. Methods: Two 2-week Online Communities were run in parallel in the UK and in the USA, including COPD patients with persistent cough and excessive mucus. Patients anonymously posted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 24 publications
(27 reference statements)
1
36
1
Order By: Relevance
“…The findings from the SML study showed that cough and mucus production were the symptoms affecting quality of sleep, work, and daily activities irrespective of severity of disease [6]. These findings also revealed that relief from cough, mucus production, and shortness of breath would be the most desirable aspects of disease management from a patient perspective (Table 2) [6,7].…”
Section: Obbmentioning
confidence: 95%
See 4 more Smart Citations
“…The findings from the SML study showed that cough and mucus production were the symptoms affecting quality of sleep, work, and daily activities irrespective of severity of disease [6]. These findings also revealed that relief from cough, mucus production, and shortness of breath would be the most desirable aspects of disease management from a patient perspective (Table 2) [6,7].…”
Section: Obbmentioning
confidence: 95%
“…The detailed findings from the qualitative online insight gathering approaches (SML and OBB studies) in COPD have been reported in their respective full publications [6,7]. In short, the results of these studies indicated that besides dyspnoea and exacerbations, cough and mucus production are very important aspects of the disease for COPD patients.…”
Section: Obbmentioning
confidence: 99%
See 3 more Smart Citations